REVITALISASI PENDIDIKAN ISLAM DALAM MEMBENTUK KARAKTER KRITIS PADA ERA POST-TRUTH SOCIETY - Zakia Indana Zulfa; Fathurrahman Muhtar; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the revitalization of Islamic education in developing critical character in the post-truth society era. The post-truth phenomenon is characterized by the dominance of opinion over fact, the increasing spread of hoaxes, the manipulation of public emotions, and social and religious polarization that develops through digital media. These conditions have resulted in low critical literacy among the younger generation and an increased tendency to accept information without adequate verification. This study uses a qualitative approach with library research methods. Data sources were obtained from SINTA and Scopus indexed journal articles, academic books, and scientific documents relevant to the research theme. Data collection techniques were carried out through literature and documentation studies, while data analysis used content analysis and descriptive-critical analysis. The results of the study indicate that Islamic education has a strong philosophical foundation in developing critical character through the concepts of tabayyun, ijtihad, tafakkur, and strengthening social ethics. However, the practice of Islamic education still tends to be normative-doctrinal, so it has not been optimal in developing students' critical thinking skills. Therefore, revitalizing Islamic education is necessary through the integration of digital literacy, the development of dialogic learning, and the transformation of educational paradigms to be more contextual and adaptive to developments in information technology. This study concludes that Islamic education plays a strategic role in shaping a generation that is religious, critical, moderate, and responsible in facing the challenges of a post-truth society.